Answer:
2 seconds
Step-by-step explanation:
Given
h = - 32t² + 64t
When the frisbee lands the height h = 0, that is
- 32t² + 64t = 0 ( multiply through by - 1 )
32t² - 64t = 0 ← factor out 32t from each term
32t(t - 2) = 0
Equate each factor to zero and solve for t
32t = 0 ⇒ t = 0
t - 2 = 0 ⇒ t = 2
t = 0 represents when the frisbee was thrown
and t = 2 when it lands
Hence it takes 2 seconds for the frisbee to land.
The expression x( x - 4 ) when expanded is x² - 4x
An expression, often known as a mathematical expression, is a finite collection of symbols that are well-formed in accordance with context-dependent principles.
When a bracket is expanded, each term is multiplied by the expression outside of the bracket.
The distributive property states that multiplying the sum of two or more addends by a number yields the same outcome as multiplying each addend separately by the number and combining the resulting products.
Consider the expression,
x( x - 4 )
Let us assume y = x( x - 4 )
Using the distributive property, a( b + c ) = ab + ac
y = x( x - 4 )
y = x · x - x · 4
y = x² - 4x
Therefore, x( x - 4 ) = x² - 4x
Therefore, the expression when expanded is x² - 4x.
Learn more about expression here:
brainly.com/question/1859113
#SPJ1
Answer:
3
,
4
,
56
,
−
79
,
82
,
0
Step-by-step explanation:
Answer:
Step-by-step explanation:
we know that
The compound interest formula is equal to
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest in decimal
t is Number of Time Periods
n is the number of times interest is compounded per year
in this problem we have
substitute in the formula above